PENINGKATAN KETERAMPILAN SISWA SEKOLAH DASAR DALAM MENULIS - Kastam Syamsi (Jurnal Kependidikan, 1999)
The purpose of this study arc (l) to tmprave the Elementary Schooi srudentsi anirude toward teaching writing, and (2) to irrrprro" the Elementary Schoot sfiidents' writing skill' Thk-swdy is held a the srudenti of grade 4 of Sapen Ekmcntary School Yogyakana. The action process is catied out in one cycle' Giieralty, this srudy k ananged as  finding  fotlowed:  (1) the goal: ih,, opprrorh in order to improve the elementary sclwol -srude*s,  antiae nward teaching writing and to improve their writing skilt,  (2) ime: t5 clnssess meeting, (3) person: leryre  (4) general action: identifying the probkms of elemcntary scttool studcnts' aniade and ind Indotnesinn  grade  founh  rcacher,  to*oia iachiig writing and their writing skill, plnnning.the action, inpleienting the action (thU is the use of a writing process approach in teaching witing including the steps of 'pr*witin[,'  'toing,  drafting, revising, editing, and publishing),moni- dataaiig, and reflecting. The monitaring instruments is obseltation sheet, whereas the evalaging instrument are writing test and questbner. The resuh of thk study are (l) the writing process approach in teaching writing is able to improve the 'elementary^  school students' axirude nward teaching writing and their writing skitt,  (2) in contcting the writinY process, there are some students hbve dfficulties a revising and editingsteps so the teacher has a role in hetping them to revise and edit their works, and  (3) there are impacts of implementing the action those are thw the students hwe pa,nicipae at reading and speaking activities so they coutd improve their another language skills'